Non-invasive brain stimulation combined with three rehabilitation approaches for cognitive and emotional well-being in Parkinson’s patients - Fan, Qianqian; Lin, Xinyu; Li, Haojie; Li, Lan (Frontiers in Neurology, 2025)
BackgroundParkinson’s disease progressively impairs both motor and non-motor functions, with over 60% of patients developing cognitive decline and nearly half suffering from depression or anxiety. While dopaminergic therapies inadequately address these symptoms, traditional rehabilitation shows inconsistent results due to impaired neuroplasticity. Non-invasive brain stimulation (tDCS/rTMS) may enhance rehabilitation by modulating neural activity, but the optimal combined approaches remain unclear. This study evaluates three rehabilitation strategies paired with brain stimulation to improve cognitive and emotional outcomes in Parkinson’s patients.MethodsWe systematically searched PubMed, Web of Science, EMBASE, Cochrane Library, and China National Knowledge Infrastructure (CNKI), ultimately including 7 randomized controlled trials (15 interventions, N = 325 Parkinson’s patients). Outcomes assessed cognitive function and emotional well-being measures. Using STATA 18.0, we conducted a network meta-analysis to evaluate relative intervention effects and assess consistency between direct/indirect evidence. Results visualized through network plots and ranked by SUCRA probabilities.ResultsThe analysis revealed that cognitive rehabilitation combined with non-invasive brain stimulation (CR) showed superior efficacy for cognitive improvement (SMD = 4.88, 95% CI [−1.91, 11.67]; SUCRA = 81.2), while combined motor-cognitive rehabilitation (MCR) excelled in emotional well-being (SMD = 4.76, 95% CI [2.70, 6.82], p < 0.00001; SUCRA = 99.5). CR for cognitive benefits and MCR for emotional regulation, with CR demonstrating the most stable treatment effects.ConclusionThis study demonstrates that non-invasive brain stimulation combined with cognitive rehabilitation (CR) is the most effective approach for improving cognitive function in Parkinson’s patients, while combined motor-cognitive rehabilitation (MCR) shows particular efficacy for emotional well-being. The findings support personalized intervention strategies: CR for cognitive impairment and MCR for emotional symptoms. Future research should optimize combined protocols to enhance synergistic effects while minimizing patient burden. This evidence-based recommendation provides important guidance for clinical practice in managing Parkinson’s non-motor symptoms.